(untitled) (Polifonia, 1994)
ABSTRACT: The aim of this paperis to analyse and interpret João Guimarães Rosa’s text called "Curtamão". Curtamão" is as narrative that synthesizes the principal modern processes of writing. It reveals a plurality of the "grammar" of forms: poetry, music, architecture, theatre, cinema and painting interacting at the level of the narrative expression, besides the intra/intertextual references.